2018
DOI: 10.1186/s12882-018-0858-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of recurrent immunoglobulin a nephropathy using steroid pulse therapy plus tonsillectomy 10 years after kidney transplantation: a case presentation

Abstract: BackgroundBoth prevention and treatment of recurrent immunoglobulin A nephropathy (IgAN) in kidney transplant recipients are important since recurrent IgAN seems to affect long-term graft survival. We present here a case of recurrent IgAN that was successfully treated using steroid pulse therapy plus tonsillectomy 10 years after kidney transplantation.Case presentationA 46-year-old male was admitted for an episode biopsy with a serum creatinine level of 1.8 mg/dl and proteinuria (0.7 g/day). Histological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Various treatment strategies have been tried with poor outcomes, including pulse steroids, cyclophosphamide per os, plasma exchange and intensification of immunosuppressive regimen [7,10]. Recently, Herzog et al reported the use of eculizumab with no effect [19], while Katsumata et al presented a patient with crescents in only 10% of the glomeruli, that achieved remission with tonsillectomy and steroid pulse therapy [20]. Our patient received pulse steroids and six monthly doses of intravenous cyclophosphamide.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Various treatment strategies have been tried with poor outcomes, including pulse steroids, cyclophosphamide per os, plasma exchange and intensification of immunosuppressive regimen [7,10]. Recently, Herzog et al reported the use of eculizumab with no effect [19], while Katsumata et al presented a patient with crescents in only 10% of the glomeruli, that achieved remission with tonsillectomy and steroid pulse therapy [20]. Our patient received pulse steroids and six monthly doses of intravenous cyclophosphamide.…”
Section: Discussionmentioning
confidence: 83%
“…The presence of crescents is even rarer in allograft kidneys, although it has been reported in 4-14% of recurrent or de novo allograft IgAN in Asian patients [9,10]. Several case reports [11][12][13][14][15][16][17][18][19][20] and two case series have been published [7,10] (Table 1). It appears to be a male predominance and the only factor associated with the development of crescentic IgAN is the presence of IgAN in native kidneys that led to ESRD [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…No established therapy is currently available for recurrent IgAN. However, some Japanese researchers reported the efficacy of tonsillectomy with or without methylprednisolone pulse therapy for recurrent IgAN [ 30 33 ]. These studies show that tonsillectomy has improved hematuria, proteinuria, and pathological manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with higher TLR9 expression in the tonsils had a lower serum Gd-IgA1 level, and hematuria improved immediately after tonsillectomy [37]. Similarly, for IgAN patients undergoing kidney transplantation, tonsillectomy has also been reported to decrease proteinuria and induce clinical remission in recurrent IgAN or IgA vasculitis [38][39][40][41]. However, tonsillectomy did not improve the outcomes of kidney transplantation in European IgAN, suggesting that the underlying mechanisms of Gd-IgA1 production may differ among ethnic groups.…”
Section: Perspectives On Preventive and Therapeutic Strategies For Ig...mentioning
confidence: 99%